PENGARUH PERCEIVED CAREER SUPPORT DAN CAREER ADAPTABILITY TERHADAP WORK PERFORMANCE YANG DI MEDIASI OLEH WORK ENGAGEMENT PADA ASN DI INSTANSI PEMERINTAHAN KOTA BANDA ACEH - astari astari; Hamdi Harmen (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
This study aims to determine the relationship between perceptions of career support and career adaptation to performance with work engagement as a mediation. Data were obtained through a survey of 351 people as a representative sample of the research population. The data analysis method used is Statistical Product and Service Solutions (SPSS). The results of the study found that perceptions of career support, career adaptability and job involvement directly affect work performance. The results also found that the perception of career support and career adaptability affects the mediator variable, namely work engagement, so that work engagement is able to become a mediator on the relationship between the variable perception of career support and career adaptation to performance.